2010
DOI: 10.4103/0973-6131.66773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga on quality of life of CLBP patients: A randomized control study

Abstract: Context:In two of the earlier Randomized Control Trials on yoga for chronic lower back pain (CLBP), 12 to 16 weeks of intervention were found effective in reducing pain and disability.Aim:To study the efficacy of a residential short term intensive yoga program on quality of life in CLBP.Materials and Methods:About 80 patients with CLBP (females 37) registered for a week long treatment at SVYASA Holistic Health Centre in Bengaluru, India. They were randomized into two groups (40 each). The yoga group practiced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(118 citation statements)
references
References 26 publications
(31 reference statements)
2
109
1
Order By: Relevance
“…14 It is also higher than that reported for women with cervical squamous metaplasia (13), 20 patients after total laryngectomy (14), 19 and patients who have survived a cerebrovascular accident (12). 21 Our PSS-10 score was lower, however, than that reported for patients with chronic lower back pain (19), 22 chronic prostatitis/chronic pelvic pain syndrome (19), 23 and irritable bowel syndrome (26). 24 One might surmise that conditions associated with chronic pain that have poor therapeutic options are associated with higher stress levels.…”
contrasting
confidence: 79%
“…14 It is also higher than that reported for women with cervical squamous metaplasia (13), 20 patients after total laryngectomy (14), 19 and patients who have survived a cerebrovascular accident (12). 21 Our PSS-10 score was lower, however, than that reported for patients with chronic lower back pain (19), 22 chronic prostatitis/chronic pelvic pain syndrome (19), 23 and irritable bowel syndrome (26). 24 One might surmise that conditions associated with chronic pain that have poor therapeutic options are associated with higher stress levels.…”
contrasting
confidence: 79%
“…To our knowledge, this is the first time, the effect of integrated yoga therapy on arterial stiffness measured at the radial artery has been assessed. We have identified IAYT as an intervention for our study as previous studies with IAYT had shown significant improvements in the overall health of the patients [7,8] . The pilot study reported initial evidence of reduced arterial stiffness along with reduced BMI in young adults with obesity after 1 week of IAYT intervention.…”
Section: Resultsmentioning
confidence: 99%
“…can be well understood with the help of the Panchakosa model [1] . The integrated approach of yoga therapy (IAYT) developed by S-VYASA is a holistic approach to treat the diseases at all the layers of human existence and the studies based on IAYT have shown significant results in improving the overall status of health, which emphasizes the importance of holistic treatment rather than focused treatment [2][3][4][5][6][7][8] . The IAYT program includes therapies based on yoga, Ayurveda and naturopathy.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized control study comparing the effect of yoga on pain and spinal flexibility in 80 subjects with chronic low-back pain group with a physical exercise group found positive results [85] . The yoga program consisted of physical postures, Pranayama , meditation, and philosophical lessons on yoga for a period of 1 week.…”
Section: Yoga For Chronic Low Back Painmentioning
confidence: 99%